A novel smart assistive knee brace incorporated with shape memory alloy wire actuator. (August 2020) - Moslemi, Navid; Gohari, Soheil; Mozafari, Farzin; Zardian, Mohsen Gol; Burvill, Colin; Yahya, Mohd Yazid; Ayob, Amran
The knee plays a significant role in locomotion and stability of the entire body through supporting the body weight and assisting the lower body kinematics during walking. However, the knee is at constant risk of becoming weakened due to disease, age, and accidents. One approach to treating weakened knee is wearing an assistive knee brace. To design a clinical knee brace, many factors such as weight and compliant mechanism should be considered. In this study, a novel smart assistive knee brace mechanism incorporated with wire actuators made of shape memory alloys is proposed to ameliorate the issues associated with weight and flexibility of existing brace designs. Unlike earlier studies, the proposed orthosis includes pressure sensor, shape memory actuator, and smart linkage. Furthermore, two distinct shape memory alloy actuator design concepts with improved stiffness are developed, and the best option is chosen systematically and prototyped. The novel mechanism proposed in this research overcomes the weight of the lower limb during swing phase using the combined shape memory alloy actuation and feed-forward controller design. As such, it can be used as a potential replacement to its conventional counterparts when the higher weight reduction as well as a flexible and controllable mechanism are simultaneously sought.